2018
DOI: 10.1108/nfs-06-2017-0108
|View full text |Cite
|
Sign up to set email alerts
|

Beet and orange mixed juices added with Lactobacillus acidophilus

Abstract: Purpose The purpose of this study was to evaluate beet and orange mixed juices added with lyophilized Lactobacillus acidophilus probiotic culture. Design/methodology/approach Two formulations of probiotic beet and orange mixed juices (1:1 e 1:2 v/v) were prepared, stored at 4°C for 28 days and were evaluated for probiotic survival, physicochemical stability, antioxidant activity and sensory acceptance. The probiotic culture was added in a lyophilized form and was not propagated in culture media or juice. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…Fruits and vegetables have been proven to support the survival of probiotics, thanks to their high sugar and total antioxidant content and relatively low pH values. In fruit juices, probiotic cultures could be added as biomass ( 8 , 9 ) or through direct addition of lyophilized cultures ( 10 ). However, these methods besides being time consuming, requiring specific equipment (as refrigerated centrifuges) and specialized operators ( 8 ), can reduce the microbial viability and impair sensory properties ( 11 – 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Fruits and vegetables have been proven to support the survival of probiotics, thanks to their high sugar and total antioxidant content and relatively low pH values. In fruit juices, probiotic cultures could be added as biomass ( 8 , 9 ) or through direct addition of lyophilized cultures ( 10 ). However, these methods besides being time consuming, requiring specific equipment (as refrigerated centrifuges) and specialized operators ( 8 ), can reduce the microbial viability and impair sensory properties ( 11 – 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…The results indicate that the processing and storage of the beverages were suitable, as vitamin C is an unstable compound and prone to oxidation, it breaks down easily and degrades steadily during storage (Kashudhan et al, ). Furthermore, the phenolic compounds are sensitive to oxidation when exposed to oxygen, heat, and light (Porto, Okina, Pimentel, Garcia, & Prudencio, ). The use of glass flasks and the low storage temperature (7°C) may have contributed to the preservation of vitamin C and TPC (Miranda et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the phenolic compounds are sensitive to oxidation when exposed to oxygen, heat, and light (Porto, Okina, Pimentel, Garcia, & Prudencio, 2018). The use of glass flasks and the low storage temperature (7°C) may have contributed to the preservation of vitamin C and TPC .…”
Section: Oligofructose Content Bioactive Compounds and Antioxidanmentioning
confidence: 99%
“…CBJ's mean flavour score may have been attributed to the samples earthy, slightly sweet and subtle flavour which was "slightly liked" by evaluators. A recent study by Porto et al (2018) sought to develop a beet and orange mixed probiotic functional beverage with L. acidophilus culture as well as evaluate its consumer acceptance, product stability and antioxidant activity. In this study, researchers reported satisfactory scores for colour, aroma, flavour and overall acceptance (Porto et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Porto et al (2018) sought to develop a beet and orange mixed probiotic functional beverage with L. acidophilus culture as well as evaluate its consumer acceptance, product stability and antioxidant activity. In this study, researchers reported satisfactory scores for colour, aroma, flavour and overall acceptance (Porto et al, 2018). Colour was found to have the highest score among panellists, which researchers attributed to the intensity and attractiveness of the colour betalains (Porto et al, 2018).…”
Section: Discussionmentioning
confidence: 99%